Poorer functionality is related to better quality of life response following the use of biological drugs: 6-month outcomes in a prospective cohort from the Public Health System (Sistema Único de Saúde), Minas Gerais, Brazil. (June 2014) - de Oliveira Junior, Haliton Alves; dos Santos, Jéssica Barreto; Acurcio, Francisco Assis; Almeida, Alessandra Maciel; Kakehasi, Adriana Maria; Alvares, Juliana; de Carvalho, Luis Fernando Duarte; Cherchiglia, Mariangela Leal
<x xml:space="preserve">Abstract</x> We aim to analyze factors associated with the quality of life (QOL) response of individuals with rheumatic diseases treated by the Public Health System (Sistema Único de Saúde) with biological disease-modifying antirheumatic drugs (bDMARDs). Data from 428 patients using bDMARDs were collected using a standardized form at baseline and 6 months after the onset of treatment. The average reduction of the scores on EuroQol-five dimension was 0.11 ± 0.18 6 months after the onset of treatment with bDMARDs, denoting significant improvement of the participants' QOL. All the investigated types of disease exhibited significant improvement at the 6-month assessment, without any difference among them (p = 0.965). The participants with baseline poorest functionality and best QOL exhibited the best QOL outcomes after 6 months of treatment. Our study showed that the use of biological drugs induced considerable improvement in the participants' QOL.